Experimental research of the enamel surface of a tooth after different kinds of treatmen - Gileva, O.S.; Muraveva, M.A.; Svistkov, A.L.; Izyumov, R.I.; Levitskaya, A.D. (Perm Federal Research Centre Journal, 2017)
Enamel demineralization still remains one of the serious undesirable effects of fixed orthodontic appliance therapy, despite techniques and material advances in preventive dentistry and orthodontics. The study was undertaken to evaluate the results of the post-orthodontic white spot lesion treatment, using a new approach based on the combination of caries infiltration technique with application of durable Fluoride-releasing enamel protective coating.